Strategi Pemasaran Berbasis Komunitas: Meningkatkan Perekonomian Desa Melalui Gerabah Plumpungrejo - Prasetyo, Andreas Recki; Agrina, Camelia Rizki (Penerbit Widina, Widina Media Utama, 2025)
This community service activity aims to optimize the marketing of Plumpungrejo Village's pottery products by strengthening managerial capacity and effective marketing strategies. Plumpungrejo Village, one of the Brilliant 2023 Villages, has excellent potential in high-quality pottery products that reflect traditional art. However, the village faces challenges in marketing, such as limited capital, market access, and digital marketing capabilities. This activity includes training for BUMDes Artha Mulya managers and MSME players, including an understanding of the Business Model Canvas (BMC), SWOT analysis, and implementation of the 7P strategy. The mentoring and training methods were conducted through in-depth interviews with relevant parties and data collection using primary and secondary data. As a result, participants were able to formulate strategies that included product diversification, expansion of distribution through marketplaces and social media, and strengthening creative promotions such as the